Biological Nitrification-Denitrification in The Drinking Water Treatment Process: Current Status and Main Biological Agents - Kravchenko, Oleksandr; Panchenko, Olena; Motronenko, Valentina; Smilianets, Evheniia (Innovative Biosystems and Bioengineering, 2018)
Background. Nitrogen compounds are one of the most common pollutants of groundwater in Ukraine. The high content of nitrates in drinking water poses a threat to the health of the population (causes methemoglobinemia in children). Ammonium compounds do not have a direct effect on the population health, but have possible effect on the drinking water organoleptic parameters (taste and smell), on the process of water disinfection and occurrence of nitrites in water distribution systems. Hence the study and the search for possible ways of using biotechnological methods of removing nitrogen compounds from drinking water in a similar way to those that occur during wastewater treatment is urgent. Objective. The aim of the paper is to review modern technologies for removing nitrogen compounds from drinking water and to systematize biological agents that are used during the process to assess the prospects for using biotechnological methods for removing nitrogen compounds at domestic water supply and sanitation facilities. Methods. A study of the current state of biological nitrification-denitrification in the purification of drinking water was carried out by reviewing the scientific literature on the application of modern biotechnological methods of nitrification-denitrification of drinking water. Results. The analysis showed that for the heterotrophic process, the presence of a carbon source is necessary, for autotrophic – a study to find the optimal electron donor. Conclusions. For the wide use of biofilters to remove nitrogen compounds from drinking water, it is necessary to seek ways to improve their work by replacing the biological agent, intensifying nitrification-denitrification processes, using mutant strains of microorganisms isolated from the loading of working filters.